Biogenic Amines in Wine: Understanding the Headache - Smit, A.Y.; du Toit, W.J.; du Toit, M. (South African Journal of Enology and Viticulture, 2016)
The presence of biogenic amines in wine is becoming increasingly important to consumers and producers alike, due to the potential threats of toxicity to humans and consequent trade implications. In the scientific field, biogenic amines have the potential to be applied as indicators of food spoilage and/or authenticity. Biogenic amines can be formed from their respective amino acid precursors by various microorganisms present in the wine, at any stage of production, ageing or storage. To understand the large number of factors that could influence the formation of biogenic amines, the chemical, biochemical, enzymatic and genetic properties relating to these compounds have to be considered. Analytical and molecular methods to detect biogenic amines in wine, as well as possibilities that could enable better control over their production levels in wine will also be explored in this review.